Multiple measures of HPA axis function in ultra high risk and first-episode schizophrenia patients. (June 2018) - Nordholm, Dorte; Rostrup, Egill; Mondelli, Valeria; Randers, Lasse; Nielsen, Mette Ø.; Wulff, Sanne; Nørbak-Emig, Henrik; Broberg, Brian V.; Krakauer, Kristine; Dazzan, Paola; Zunszain, Patricia A.; Nordentoft, Merete; et al.
Highlights: Cortisol reactivity was increased in ultra high-risk patients. Patients experienced more perceived stress and life events compared with the healthy controls. Cortisol reactivity in ultra high-risk patients was inverse correlated with subthreshold psychotic symptoms. There was no difference in pituitary gland volume between groups. Abstract: Introduction: Abnormalities within hypothalamus-pituitary-adrenal (HPA) axis might interact with other neurobiological systems to enhance the risk of psychosis. Most of the neurodevelopmental and HPA axis changes occur in adolescence; this is also the period when prodromal and psychotic symptoms occur for the first time. More knowledge about how various stress components interact can advance understanding of the link between psychosis and the HPA axis. Method: We examined 41 ultra high-risk (UHR) patients and 40 antipsychotic-naïve first-episode schizophrenia (FES) patients and compared them with 47 matched controls. The Perceived Stress Scale and the Recent Life Events Questionnaire were used to assess the stress levels. Day-time saliva samples were taken to measure cortisol. The pituitary gland volume was measured manually on the structural MRI using stereology. Results: Only the UHR patients, had a higher cortisol increase just after awakening (p = 0.009) compared to healthy controls. In UHR patients, we found a negative correlation between cortisol increase after awakening and symptom severity (p = 0.008). Pituitary gland volume and diurnal cortisol were not significantly different among the three groups. There was no correlation between pituitary gland volume, perceived stress/recent life events and any of the cortisol measures or symptoms. Conclusion: Symptom severity during the very early phase of illness (UHR) seems to be associated with altered cortisol increase. Longitudinal studies in UHR patients would be useful to examine how stress levels affect the course of the illness.